INVESTIGATION OF CHILDREN AS A CRIMINAL CONDUCT OF DEATH LEADING ABUSE (A CASE STUDY IN THE LEGAL AREA OF THE BULELENG RESORTS POLICE) - Tjok Istri Nirwikara .R.; Ni Putu Rai Yuliartini; Dewa Gede Sudika Mangku (Jurnal Pendidikan Kewarganegaraan Undiksha, 2020)
This study discusses to analyze, the implementation of research on children who oppose criminal acts of persecution carried out in the jurisdiction of the Buleleng Resort Police and the protection needed by investigators in the process of investigating children. This research uses empirical research, with descriptive research types, data and data sources are divided into primary data and secondary data consisting of primary legal materials, secondary materials and tertiary materials, then using data merging techniques with document study techniques, observation techniques, and interview technique, in the sample selection technique using non-probability sampling techniques, namely purposive sampling, the data of this study were processed and analyzed qualitatively presented in a descriptive qualitative manner. The location of the study was conducted at the Buleleng Police Station. The subjects of this study were the parties involved in the study involving deaths carried out by minors. The results showed that the investigation carried out in accordance with the juvenile justice system, the investigation continues to prioritize child protection. Related to what is broadcast by the investigator during the process of education which is well done which is carried out with the consent of the children but concerns issues that are classified as minors who have been known in advance from the time limit for conducting the investigation which is demanded quickly will lead to investigators in terms of looking for evidence, witnesses, questions and answers.